Removal of Ni2+ and Cd2+ from Aqueous Solution Using Iranian Natural Bentonite - Hashemi, Kh.; Zahiri, R.; Ebadi, A.G. (Asian Journal of Chemistry, 2013)
Bentonites consist clay minerals of the smectite group have a wide range of industrial uses. A particular feature of this group of minerals is the substitution of Si4+ and Al3+ in the crystal structure by lower valency cations. The structure, chemical composition, exchangeable ion type and small crystal size of smectite are responsible for several unique properties. In this study by using chemical analysis analysis methods e.g.; XRD, XRF, SEM, the kind of Reshm natural bentonite mine have been determined as montmorillonite and clinoptilolite. Then the ability of bentonite to reomove heavy metal ions from wastewater and its factors affecting it have been examined. The batch sorption experiments of Ni2+ and Cd2+ were conducted on Na-bentonite under various conditions. Adsorption behaviour of bentonite was strongly depending on pH, initial concentration, time and temperature. The removal rate of bentonite decreases with an increase in the initial metal ion concentration. pH for removal of Ni2+ is 4 and for Cd2+ is 5.